Modification, Characterization of New Thiazolidinone and Oxazolidinone Derived from Levofloxacin and Evaluation of Anti-Oxidant - Moaied Rabeaa, Mustafa; Muna Ismael Khalaf,; Farouk Abdulla Kandil , (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The research study included the synthesis of a new series of heterocyclic derivatives containing the antibiotic Levofloxacin. The first way provides for the reaction of  Levofloxacin with thionyl chloride in benzene as a solvent to give an acid chloride derivative. A new class of acid hydrazide synthesized from Levofloxacin was studied. Schiff bases were produced via the reaction of acid hydrazide with substituted aromatic ketones in methanol. The next stage involved the response of Schiff bases with thioglycolic acid and mono chloroacetic acid in DMF to produce derivatives of the antibiotic levofloxacin that have five heterocyclic members, including the derivatives thiazolidine-4-one and oxazolidine-5-one. The FTIR, 1HNMR, and 13CNMR spectra methods were used to confirm the structures of newly synthesized compounds. Also, the antioxidant properties of the synthetic compounds were evaluated in vitro. According to this study, levofloxacin-derived compounds have higher antioxidant capacities than ascorbic acid (vitamin C), and the medication also acts as an anti-inflammatory for respiratory infections.